Recurrent cerebral abscess in tetralogy of Fallot - Wanty Sahli; J M Ch Pelupessy (Indonesian Pediatric Society, 2004)
Tetralogy of Fallot (TF) classically consistsof the combination of right ventricularoutflow obstruction (pulmonary stenosis),ventricular septal defect (VSD), overridingaorta, and right ventricular hypertrophy. Thedegree of pulmonary stenosis and VSD determine thevariety of clinical manifestations.This type of congenital heart disease accountsfor about 10% of all congenital cardiac deformitiesand is the most common cyanotic lesion after thefirst year of life. Cerebral abscess is a serious com-plication in TF and is usually seen after the age of 2years.